The equation I have is 3(dy/dx) + 4y = 4 +6x + 4x^2
I am given that y = 1 when x = 0.
Basically, I can do the initial transform, but afterwards I get completely cnofused. Any help is appreciated.
Ok what I have done is take L.T's, which gives me this:
dont know what the symbol here is but its always Y bar
3(sy - 1) +4y = 4/s + 6/s^2 + 8/s^3
So then I get:
y(3s + 4) = 4/s + 6/s^2 + 8/s^3 + 3
I dont know how to proceed from here. I could obviously divide the rand hand side by (3s+4) but im not completely certain if I need to do anything else first.